In Vitro Systems for the Study of Hepatitis C Virus Infection - Garrick K. Wilson; Zania Stamataki (International Journal of Hepatology)
The study of a virus is made possible by the availability of culture systems in which the viral lifecycle can be realized. Such systems support robust virus entry, replication, assembly, and secretion of nascent virions. Furthermore, culture models provide a platform in which therapeutic interventions can be devised or monitored. Hepatitis C virus (HCV) has a restricted tropism to human and chimpanzees; thus investigations of HCV biology have been hindered for many years due to a lack of small animal models. Nevertheless, significant efforts have been directed at developing cell culture models to elucidate the viral lifecycle in vitro. HCV primarily infects liver parenchymal cells commonly known as hepatocytes. The liver is a highly specialized and complex organ and the development of in vitro systems that reflects this complexity has proven difficult. Consequently, host cell receptor molecules that potentiate HCV infection were identified over a decade after the virus was discovered. A summary of the various HCV in vitro culture models, their advantages, and disadvantages are described.